Isomerization of Keggin Al13 Ions Followed by Diffusion Rates. Issue 52 (29th November 2016) - Oliveri, Anna F.; Colla, Christopher A.; Perkins, Cory K.; Akhavantabib, Noushin; Callahan, Joseph R.; Pilgrim, Corey D.; Smart, Scott E.; Cheong, Paul H.‐Y.; Pan, Long; Casey, William H.
Abstract: Invited for the cover of this issue is a group of researchers from the University of California Davis, Colgate–Palmolive Company, and Oregon State University. The image depicts aluminum ions as silver spheres, oxygen atoms as red spheres, carbon as black spheres, and nitrogen as green spheres. Hydrogen atoms were omitted for clarity. Read the full text of the article, which also includes insight on the other aluminum clusters that glycine stabilizes, at10.1002/chem.201604640 . Abstract : " Our group wanted to understand the role of glycine in the isomerization of the Al13 Keggin clusters ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 18682 ff. (DOI:10.1002/chem.201604640 ).